Implementasi Green Supply Chain Management untuk Pasokan Telur Ayam Menggunakan Metode Fuzzy AHP - Agung Prayudha Hidayat; Sesar Husen Santosa; Derry Dardanella (Industrial Engineering, Engineering of Faculty, Universitas Kadiri, 2023)
The need for chicken eggs is inseparable from the supply chain network. Green aspects in fulfilling supply chain networks have an impact on the environment such as market cleanliness and egg quality. The current condition of Kemang Market in supply chain management has not led to environmental aspects. The purpose of this study is to identify priority criteria that can be applied to green supply chain management activities in Kemang Market, Bogor Regency. The method used is Fuzzy Analytical Hierarchy Process (AHP) to determine the main criteria in applying green supply chain management practices to chicken eggs in Kemang Market, Bogor Regency. The results showed that the main criteria used in the GSCM practice of chicken eggs are top management support in implementing supply chain operational activities, namely through clean market environment programs and monitoring systems related to egg arrival and dispensing systems in the market.